Analytical study on the extent of the impact of modern technology on the management of sports institutions - د. محـمـد رافـت بـيومي أ.د. ناهــدة عبد زيد الدليمي (الرياضة المعاصرة)
The use of computers has become widespread in recent times in various fields and has proven efficient and saved a lot of effort, time and cost, including the sports field, which is the subject of the study aimed at the extent of the impact of modern technology in managing sports institutions and institutions here we mean, for example, but not limited to         Ministries of Youth and Sports - Olympic committees - sports federations - sports clubs  Sports institutions have an important role in educating children and youth and preparing them as good citizens through sports programs that implement their goals among the general objectives of the state The necessity of management for teachers - supervisors - administrators so that each of them works consciously to achieve the goals of the institution.It helps to identify the problems and obstacles and to predict the expected possibilities and circumstances to make the methods and procedures of work in the sports field more